Impact of the COVID-19 pandemic on community antibiotic prescribing in Scotland. Issue 4 (8th December 2020) - Malcolm, William; Seaton, Ronald A; Haddock, Gail; Baxter, Linsey; Thirlwell, Sarah; Russell, Polly; Cooper, Lesley; Thomson, Anne; Sneddon, Jacqueline
Abstract: Background: Following concerns about increased antibiotic use during the COVID-19 pandemic, trends in community antibiotic prescriptions in Scotland were evaluated. Methods: The primary care prescription electronic messaging system used in GP practices with NHS contracts provided near real-time data analysis of national data. The main outcome measures were the weekly number of prescriptions for antibiotics generated by prescribers in GP practices in 2020 compared with 2019. Results: At end of Week 12 2020 (22 March), after a sharp increase, the number of prescriptions commonly used for respiratory infections was 44% higher than the corresponding week in 2019. The number of prescriptions for respiratory antibiotics reduced through April and May 2020, with 34% fewer prescriptions issued by end of Week 22 (31 May) than in the corresponding week in 2019. Reductions were pronounced in all age groups but particularly apparent for prescriptions for children aged 0–4 years. These data were compared with weekly prescriptions for a selection of non-respiratory antibiotics and no difference was seen between 2020 and 2019. Conclusions: Trends in antibiotic prescription data show that after an initial surge, and following 'lockdown' in Scotland, the total number of prescriptions for antibiotics commonly used for respiratory infections fell. We believe this is the first published national evaluation of the impact of COVID-19 on community use of antibiotics. Further analysis of national data is planned to provide a greater understanding of the reasons behind these trends.